Manufacturing process of semi-toughened laminated insulating glass
Patent Information
- Application Number
- CN202610983475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-03
AI Technical Summary
若夹胶界面耐湿热性能不足,水汽可能沿玻璃边部或界面微缺陷逐渐扩散,导致夹层胶片与玻璃表面结合力降低,并进一步影响中空腔体的密封稳定性
[0027](1)本发明通过对钠钙硅玻璃进行切割、磨边、倒角、洗涤、漂洗和干燥处理,能够减少玻璃边部缺口、尖锐棱角和表面残留物,降低后续急冷过程中的破裂风险,提高半钢化玻璃的加工稳定性。辛基酚聚氧乙烯醚与去离子水形成清洗液后,能够增强对油污、磨削粉尘和细小颗粒的去除作用,使待夹胶表面保持洁净,有利于界面处理液在半钢化玻璃表面均匀铺展和干燥成膜。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of architectural safety glass processing technology, specifically relating to a manufacturing process for semi-tempered laminated insulated glass. Background Technology
[0002] Semi-tempered laminated insulated glass is a commonly used composite glass material in building curtain walls, doors and windows, skylights, partitions, and safety protection structures. It is typically composed of semi-tempered glass, interlayer film, a spacer structure, drying materials, and a sealant system. Compared to ordinary annealed glass, semi-tempered glass has higher bending resistance and thermal shock resistance; compared to fully tempered glass, it has a lower risk of spontaneous breakage and better fracture preservation. The laminated structure allows the interlayer film to hold the fragments together after breakage, reducing the risk of falling and scattering. The insulated structure improves thermal insulation, sound insulation, and condensation prevention. Therefore, semi-tempered laminated insulated glass has high application value in high-rise buildings, public buildings, and energy-efficient doors and windows.
[0003] The existing manufacturing process for semi-tempered laminated insulated glass typically includes steps such as glass cutting and edging, cleaning and drying, semi-tempering treatment, lamination, autoclaving, and insulated sealing. Although this process is relatively mature, it still has several shortcomings in practical applications. On the one hand, after cleaning, heating, and rapid cooling, the distribution of surface-active groups, residual trace contaminants, and surface micro-defects on the glass surface can affect the bonding stability between the interlayer film and the glass. On the other hand, the polyvinyl butyral interlayer film itself is quite sensitive to moisture. Under conditions of humid heat, ultraviolet radiation, and thermal cycling, the laminated edges are prone to whitening, delamination, blistering, or localized decrease in adhesion. Especially after the laminated glass is further combined with the insulated structure, the edge area is simultaneously affected by the aging of the interlayer film and the aging of the insulated seal. If there is no stable interface transition layer between the glass and the interlayer film, weak areas are prone to failure during long-term use.
[0004] Furthermore, current insulated glass manufacturing processes typically rely on molecular sieves to adsorb moisture within the cavity and achieve sealing through butyl hot-melt sealant and external sealant. However, the long-term reliability of the insulated structure depends not only on the sealing material itself but also on the interface condition of the laminated glass edges. If the interfacial resistance to damp heat is insufficient, moisture may gradually diffuse along the glass edges or interface micro-defects, leading to a reduction in the adhesion between the interlayer film and the glass surface, and further affecting the sealing stability of the insulated cavity. Existing processes primarily focus on semi-tempered glass strength control, interfacial venting quality, and insulated sealant application quality, paying insufficient attention to the chemical modification and interface enhancement of the glass surface to be laminated, making it difficult to simultaneously address interfacial stability, edge resistance to damp heat, and insulated seal reliability. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a manufacturing process for semi-tempered laminated insulating glass.
[0006] A first aspect of the present invention provides a manufacturing process for semi-tempered laminated insulating glass, comprising the following steps:
[0007] S1. Cut, grind, and chamfer the soda-lime-silica glass to obtain pretreated glass; add 0.5-2.0 parts by weight of octylphenol polyoxyethylene ether to 200-300 parts of deionized water, stir, and obtain cleaning solution; wash the pretreated glass with the cleaning solution, rinse with deionized water, and dry to obtain glass to be semi-tempered.
[0008] S2. The glass to be semi-tempered is placed in a tempering furnace and heated at 650-690℃, followed by rapid cooling to obtain semi-tempered glass. By weight, 0.5-2.0 parts of cerium-zirconium-aluminum-silicon-boron complex toughening sol, 80-95 parts of anhydrous ethanol and 5-15 parts of deionized water are mixed and stirred to obtain an interface treatment solution. The interface treatment solution is coated onto the surface of the semi-tempered glass to be laminated and dried at 50-70℃ to obtain modified semi-tempered glass.
[0009] S3. Place two pieces of modified semi-tempered glass at 20-25℃. The modified semi-tempered glass has a modified surface and an unmodified surface. The modified surface is the side surface coated with the interface treatment liquid. Place one piece of modified semi-tempered glass with the modified surface facing up, and lay a polyvinyl butyral interlayer film on the modified surface. Then, place another piece of modified semi-tempered glass with the modified surface facing down on the polyvinyl butyral interlayer film, so that the polyvinyl butyral interlayer film is located between the modified surfaces of the two pieces of modified semi-tempered glass to obtain laminated glass. Roll press the laminated glass and pre-vent the air to obtain pre-vented laminated glass. Then, place the pre-vented laminated glass in an autoclave, keep it at 125-140℃, and cool it to obtain semi-tempered laminated glass.
[0010] S4. Fill the aluminum alloy spacer with 3A molecular sieve, seal the port, and apply butyl hot melt sealant to both sides of the aluminum alloy spacer. Press the semi-tempered laminated glass, aluminum alloy spacer and semi-tempered glass together to form a hollow cavity. Fill the hollow cavity with argon gas to obtain argon-filled glass. Inject two-component polysulfide sealant along the outer channel of the argon-filled glass and cure.
[0011] In this invention, during the manufacturing process of semi-tempered laminated insulated glass, the soda-lime silica glass undergoes cutting, edge grinding, and chamfering, reducing sharp edges and micro-cracks, thus minimizing stress concentration during subsequent heating and cooling processes. Octylphenol polyoxyethylene ether, when added to deionized water, forms a cleaning solution that reduces surface tension and emulsifies oily contaminants, allowing oil, grinding dust, and fine particles on the glass surface to be removed during washing and rinsing. After drying, a glass surface suitable for heat treatment and interface coating is obtained. When the semi-tempered glass is heated in a tempering furnace, both the surface and interior soften. Subsequent rapid cooling causes the surface to shrink before the interior, creating compressive stress, while the interior develops tensile stress to balance it, resulting in semi-tempered glass. A cerium-zirconium-aluminum-silicon-boron complex toughening sol is mixed with anhydrous ethanol and deionized water to form an interface treatment solution. This solution is applied to the surface of the semi-tempered glass to be laminated. During drying, the anhydrous ethanol and deionized water evaporate, and the silicon-oxygen structure, boron-oxygen structure, and zirconium, aluminum, and cerium complex structure in the sol form a continuous interface layer on the glass surface. The silanol groups in this interface layer can undergo dehydration condensation with the hydroxyl groups on the glass surface. The boron-oxygen structure and metal complex structure form hydrogen bonds, oxygen bridges, and polar interactions with the glass surface, improving the bonding stability between the modified surface and the glass substrate. During lamination, a polyvinyl butyral interlayer film is placed between the modified surfaces of the two pieces of modified semi-tempered glass. Rolling and pre-venting remove interfacial air. High-pressure autoclave heating softens the polyvinyl butyral interlayer film and fully wets the modified surface. The hydroxyl groups in the polyvinyl butyral interlayer film undergo ring-opening reactions with the glycidyl groups in the interface layer, simultaneously forming hydrogen bonds and dipole interactions, making the interfacial bonding more stable. In the hollow composite stage, aluminum alloy spacers support the hollow cavity, 3A molecular sieves adsorb residual moisture, butyl hot melt sealant forms an inner barrier, argon gas reduces heat transfer in the cavity, and two-component polysulfide sealant, after curing, forms an outer seal and edge fixation, thereby improving the edge's resistance to damp heat and long-term sealing reliability.
[0012] According to a preferred embodiment of the present invention, in step S1, the drying time is 3-8 minutes.
[0013] According to a preferred embodiment of the present invention, in step S2, the drying time at 50-70°C is 5-15 minutes.
[0014] According to a preferred embodiment of the present invention, in step S3, the heat preservation time at 125-140°C is 30-60 minutes.
[0015] According to a preferred embodiment of the present invention, in step S4, the butyl hot melt sealant is applied at a temperature of 120-140°C and cured for 24-72 hours.
[0016] According to a preferred embodiment of the present invention, the preparation steps of the cerium-zirconium-aluminum-silicon-boron complex toughening sol include:
[0017] A1. By weight, add 55-75 parts anhydrous ethanol, 18-28 parts deionized water, and 0.2-0.8 parts glacial acetic acid to a reactor and stir at 20-30°C; then add 18-26 parts tetraethyl orthosilicate and continue stirring to obtain a silicate ester pre-hydrolyzed mixture; add 4-8 parts γ-glycidoxypropyltrimethoxysilane to the silicate ester pre-hydrolyzed mixture and continue stirring; then add 0.6-1.6 parts boric acid and 0.5-1.2 parts citric acid monohydrate, and react at 35-45°C to obtain a borosilicate pre-hydrolyzed solution;
[0018] A2. Add 35-55 parts deionized water, 20-35 parts anhydrous ethanol, and 8-14 parts citric acid monohydrate to the reactor and stir. Then add 3-6 parts zirconium nitrate hydrate, 2-5 parts aluminum nitrate nonahydrate, and 0.8-2.2 parts cerium nitrate hexahydrate in sequence and continue stirring. Add 2-5 parts ethylene glycol, then add ammonia water to adjust the pH to 3.5-4.0, and heat to 45-60℃ to react and obtain a cerium-zirconium-aluminum complex solution.
[0019] A3. Add the cerium-zirconium-aluminum complex solution dropwise to the silicon-boron pre-hydrolyzed solution and stir; add ammonia water to adjust the pH to 4.0-4.5, then add 0.2-0.8 parts of polyvinylpyrrolidone and react at 45-55℃ to obtain the cerium-zirconium-aluminum-silicon-boron composite complex colloid.
[0020] A4. The cerium-zirconium-aluminum-silicon-boron composite complex colloid is aged in a sealed environment at 35-45℃ to obtain an aged colloid; the aged colloid is distilled under reduced pressure at 45-55℃ to obtain a concentrated colloid; 10-30 parts of anhydrous ethanol and 5-20 parts of deionized water are added to the concentrated colloid to adjust the pH to 4.2-4.6; then the mixture is filtered.
[0021] In this invention, the preparation of the cerium-zirconium-aluminum-silicon-boron complex toughening sol is based on the hydrolysis and condensation of tetraethyl orthosilicate. Anhydrous ethanol forms a homogeneous liquid phase with tetraethyl orthosilicate, deionized water, and glacial acetic acid. Glacial acetic acid provides a mildly acidic environment, causing the ethoxy groups of tetraethyl orthosilicate to gradually hydrolyze and generate a pre-hydrolyzed structure containing silanol groups. Subsequently, the silanol groups undergo slow dehydration and condensation to form an oligomeric siloxane network. After γ-glycidoxypropyltrimethoxysilane is added to the silicate ester pre-hydrolyzed mixture, its methoxy groups also undergo hydrolysis. The generated silanol groups continue to co-condense with the oligomeric siloxane structure, allowing the organic segments containing glycidyl groups to attach to the outside of the siloxane backbone, improving the toughness of the sol film and providing reaction sites for subsequent interfacial interactions with the hydroxyl groups in the polyvinyl butyral interlayer film. Boric acid undergoes hydrogen bonding and condensation with the silanol groups in a weakly acidic system, allowing boron to enter the siloxane network in the form of dispersed nodes, improving the density and water resistance of the film layer. Citric acid monohydrate helps maintain an acidic environment in the boron-silicon pre-hydrolysis solution, while in the cerium-zirconium-aluminum complex solution, it forms coordination structures with zirconium, aluminum, and cerium ions through its carboxyl groups. When zirconium oxynitrate hydrate, aluminum nitrate nonahydrate, and cerium nitrate hexahydrate enter a system composed of deionized water, anhydrous ethanol, citric acid monohydrate, and ethylene glycol, the carboxyl groups of citric acid monohydrate and the hydroxyl groups of ethylene glycol participate in coordination, forming a stable complex state. Adjusting the pH with ammonia water can reduce the risk of rapid hydrolysis and local precipitation of metal ions. When the cerium-zirconium-aluminum complex solution is added dropwise to the boron-silicon pre-hydrolysis solution, the silanol-containing, boronol-containing, and zirconium, aluminum, and cerium complex structures gradually recombine and condense, forming a cerium-zirconium-aluminum-silicon-boron composite complex colloid. Polyvinylpyrrolidone adsorbs onto the surface of the colloidal particles, forming a steric barrier and reducing particle aggregation. During the closed curing process, the complex colloid continues to slowly condense and rearrange; after removing some volatile components by vacuum distillation, anhydrous ethanol and deionized water are used to adjust the dispersion state of the system, and coarse aggregates are removed by subsequent filtration to obtain cerium-zirconium-aluminum-silicon-boron complex toughening sol.
[0022] According to a preferred embodiment of the present invention, in step A1, the reaction time at 35-45°C is 1-2 hours.
[0023] According to a preferred embodiment of the present invention, in step A2, the reaction time at 45-60°C is 1.5-3 hours.
[0024] According to a preferred embodiment of the present invention, in step A3, the reaction time at 45-55°C is 3-5 hours.
[0025] According to a preferred embodiment of the present invention, in step A4, the time for sealed curing at 35-45°C is 12-24 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) This invention reduces edge defects, sharp corners, and surface residues in soda-lime-silica glass by cutting, grinding, chamfering, washing, rinsing, and drying, thereby reducing the risk of breakage during subsequent rapid cooling and improving the processing stability of semi-tempered glass. Octylphenol polyoxyethylene ether, when mixed with deionized water to form a cleaning solution, enhances the removal of oil, grinding dust, and fine particles, keeping the surface to be laminated clean and facilitating the uniform spreading and drying of the interface treatment solution on the surface of the semi-tempered glass.
[0028] (2) In this invention, an interface treatment solution is prepared using a cerium-zirconium-aluminum-silicon-boron complex toughening sol, anhydrous ethanol, and deionized water. The interface treatment solution is then applied to the surface of the semi-tempered glass to be laminated. After drying, a stable interface layer is formed on the surface of the semi-tempered glass. This interface layer can improve the bonding state between the semi-tempered glass and the polyvinyl butyral interlayer film, increase the bonding strength and damp heat resistance of the interlayer, and reduce edge whitening, blistering, and delamination, thereby improving the breakage resistance and durability of the semi-tempered laminated glass.
[0029] (3) The present invention further forms a hollow cavity by using aluminum alloy spacers, uses 3A molecular sieves to adsorb residual moisture, uses butyl hot melt sealant to form an inner seal, uses argon gas to improve the thermal insulation performance of the hollow cavity, and forms an outer seal by curing a two-component polysulfide sealant. The above structures work together to give the semi-tempered laminated insulating glass good interfacial bonding stability, edge sealing stability, moisture and heat resistance, thermal insulation performance and safety retention performance, making it suitable for building doors and windows, curtain walls and lighting structures. Detailed Implementation
[0030] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0031] Example 1
[0032] This embodiment provides a manufacturing process for semi-tempered laminated insulating glass, including the following steps:
[0033] S1. Take three pieces of 6mm thick soda-lime silica glass and cut them into 300mm×300mm glass sheets. Grind and chamfer the four sides of the glass sheets to make the glass edges flat and without visible gaps, thus obtaining pre-treated glass. Weigh 1.25g of octylphenol polyoxyethylene ether and add it to 250g of deionized water. Stir at 300r / min for 10min at 25℃ to disperse the octylphenol polyoxyethylene ether evenly, thus obtaining a cleaning solution. Wash both sides of the pre-treated glass with the cleaning solution for 5min per piece. Then rinse twice with deionized water, using 250g of deionized water each time. After rinsing, place the glass in a 60℃ hot air drying oven for 5.5min to dry, thus obtaining glass to be semi-tempered.
[0034] S2. The glass to be semi-tempered obtained in S1 is placed in a tempering furnace and heated at 670℃ for 270s to achieve a semi-tempered state. Then, it undergoes rapid cooling to 35℃ to obtain semi-tempered glass. 1.25g of cerium-zirconium-aluminum-silicon-boron complex toughening sol, 87.5g of anhydrous ethanol, and 10g of deionized water are weighed and mixed. The mixture is stirred at 300r / min for 15min at 25℃ to uniformly disperse the cerium-zirconium-aluminum-silicon-boron complex toughening sol, obtaining an interface treatment solution. Two pieces of semi-tempered glass are taken, and the interface treatment solution is applied to the surface of the semi-tempered glass to be laminated using a roller coating method, with a coating amount of 10g / m². 2 The glass is dried at 60°C for 10 minutes to allow the interface treatment solution to form a modified layer on the surface of the semi-tempered glass to be laminated, resulting in two pieces of modified semi-tempered glass. One piece of semi-tempered glass is reserved for later use.
[0035] S3. Place two pieces of modified semi-tempered glass at 22.5℃ for 10 minutes. The modified semi-tempered glass has a modified surface and a non-modified surface, and the modified surface is the side surface coated with the interface treatment liquid. Place one piece of modified semi-tempered glass with the modified surface facing up, and lay 60g of polyvinyl butyral interlayer film on the modified surface, making the polyvinyl butyral interlayer film flat and adhered to the modified surface. Then, place the other piece of modified semi-tempered glass with the modified surface facing down on the polyvinyl butyral interlayer film, so that the polyvinyl butyral interlayer film adheres to the modified surface. A butyral interlayer film is placed between the modified surfaces of two pieces of modified semi-tempered glass to obtain laminated glass. The laminated glass is fed into a rolling mill and rolled at 70°C with a rolling pressure of 0.3 MPa and a rolling speed of 1.0 m / min to complete pre-venting, resulting in pre-vented laminated glass. Subsequently, the pre-vented laminated glass is placed in an autoclave and held at 132.5°C and 1.2 MPa for 45 min. After the holding period, it is cooled to 40°C, depressurized, and removed to obtain semi-tempered laminated glass.
[0036] S4. Weigh 20g of 3A molecular sieve and fill it into the aluminum alloy spacer. The aluminum alloy spacer forms a rectangular spacer frame that matches the edge of the semi-tempered laminated glass. Seal the port. Apply 30g of butyl hot melt sealant to both sides of the aluminum alloy spacer. The application temperature of the butyl hot melt sealant is 130℃. Press the semi-tempered laminated glass obtained in S3, the aluminum alloy spacer, and the spare semi-tempered glass obtained in S2 together to form a hollow cavity. Fill the hollow cavity with argon gas for 3 minutes at a pressure of 0.1MPa to obtain argon-filled glass. Inject 160g of two-component polysulfide sealant along the outer periphery of the argon-filled glass and cure it at 25℃ for 48 hours to obtain semi-tempered laminated insulating glass.
[0037] Preparation steps of cerium-zirconium-aluminum-silicon-boron complex toughening sol:
[0038] A1. Weigh 65g of anhydrous ethanol, 23g of deionized water, and 0.5g of glacial acetic acid and add them to a 500mL glass reactor. Stir at 400r / min for 10min at 25℃ to ensure the anhydrous ethanol, deionized water, and glacial acetic acid are thoroughly mixed. Then weigh 22g of tetraethyl orthosilicate and add it to the reactor over a period of 20min, maintaining stirring at 400r / min throughout the addition process. After the addition is complete, continue stirring for 40min to disperse the tetraethyl orthosilicate in the system formed by the anhydrous ethanol, deionized water, and glacial acetic acid. Pre-hydrolysis was carried out to obtain a silicate ester pre-hydrolysis mixture; 6g of γ-glycidoxypropyltrimethoxysilane was added to the silicate ester pre-hydrolysis mixture, and stirring was continued at 400r / min for 30min to ensure that the γ-glycidoxypropyltrimethoxysilane and the silicate ester pre-hydrolysis mixture were fully mixed; then 1.1g of boric acid and 0.85g of citric acid monohydrate were added, and the temperature was raised to 40℃ and reacted for 1.5h. During the reaction, stirring was maintained at 400r / min. After the reaction was completed, the temperature was cooled to 25℃ to obtain a borosilicate pre-hydrolysis solution.
[0039] A2. Weigh 45g of deionized water, 27.5g of anhydrous ethanol, and 11g of citric acid monohydrate and add them to a 500mL glass reactor. Stir at 400r / min for 20min at 25℃ to dissolve the citric acid monohydrate and form a homogeneous system. Then, add 4.5g of zirconium oxynitrate hydrate, 3.5g of aluminum nitrate nonahydrate, and 1.5g of cerium nitrate hexahydrate sequentially, stirring for 10min after each addition. After all substances are added, continue stirring for 30min to ensure that the zirconium oxynitrate hydrate, aluminum nitrate nonahydrate, and cerium nitrate hexahydrate are fully dispersed. Add 3.5g of ethylene glycol and continue stirring for 20min. Then, add ammonia dropwise to adjust the pH to 3.75, maintaining the system temperature at 25℃ during the adjustment process. Then, raise the temperature to 52.5℃ and react for 2.25h, maintaining stirring at 400r / min throughout the reaction. After the reaction is complete, cool to 25℃ to obtain a cerium-zirconium-aluminum complex solution.
[0040] A3. The cerium-zirconium-aluminum complex solution obtained in A2 was added dropwise to the silicon-boron pre-hydrolyzed solution obtained in A1. The dropwise addition time was controlled at 60 min. During the dropwise addition, the mixture was stirred at 400 r / min to ensure that the cerium-zirconium-aluminum complex solution and the silicon-boron pre-hydrolyzed solution were fully mixed. After the dropwise addition was completed, the mixture was stirred for another 30 min. Ammonia water was added to adjust the pH to 4.25. Then, 0.5 g of polyvinylpyrrolidone was added, and the mixture was stirred for another 20 min. The mixture was reacted at 50 °C for 4 h. During the reaction, the mixture was stirred at 400 r / min. After the reaction was completed, the mixture was cooled to 25 °C to obtain the cerium-zirconium-aluminum-silicon-boron composite complex colloid.
[0041] A4. The cerium-zirconium-aluminum-silicon-boron composite complex colloid obtained in A3 was transferred to a sealed container and aged at 40℃ for 18 hours to obtain an aged colloid. The aged colloid was then distilled under reduced pressure at 50℃, with the vacuum degree controlled at -0.08MPa, until the mass of the system was reduced to 85% of the initial mass of the aged colloid, to obtain a concentrated colloid. 20g of anhydrous ethanol and 12.5g of deionized water were added to the concentrated colloid, and the mixture was stirred at 300r / min for 20min to adjust the pH to 4.4. Subsequently, the mixture was filtered through a microporous membrane with a pore size of 0.45μm, and the filtrate was collected to obtain the cerium-zirconium-aluminum-silicon-boron complex toughening sol.
[0042] Example 2
[0043] The difference between this embodiment and Embodiment 1 is that this embodiment provides a manufacturing process for semi-tempered laminated insulating glass, including the following steps:
[0044] S1. Cut, grind, and chamfer the edges of the soda-lime-silicon glass to make the edges smooth, thus obtaining pre-treated glass. Weigh 0.5g of octylphenol polyoxyethylene ether and add it to 200g of deionized water. Stir to disperse the octylphenol polyoxyethylene ether evenly, thus obtaining a cleaning solution. Wash the pre-treated glass with the cleaning solution to remove grinding residues and oil stains from the surface of the pre-treated glass. Rinse with deionized water to remove residual cleaning solution. Dry for 3 minutes to obtain glass to be semi-tempered.
[0045] S2. The glass to be semi-tempered obtained in S1 is sent into a tempering furnace and heated at 650°C to achieve a semi-tempered state. Then, it is subjected to rapid cooling to obtain semi-tempered glass. Weigh 0.5g of cerium-zirconium-aluminum-silicon-boron complex toughening sol, 80g of anhydrous ethanol and 5g of deionized water, mix and stir to uniformly disperse the cerium-zirconium-aluminum-silicon-boron complex toughening sol to obtain an interface treatment solution. Coat the interface treatment solution onto the surface of the semi-tempered glass to be laminated and dry at 50°C for 5 minutes to form a modified layer on the surface of the semi-tempered glass to be laminated, thus obtaining modified semi-tempered glass.
[0046] S3. Place the modified semi-tempered glass at 20°C. The modified semi-tempered glass has a modified surface and a non-modified surface. The modified surface is the side surface coated with the interface treatment liquid. Place one piece of modified semi-tempered glass with the modified surface facing up. Lay 60g of polyvinyl butyral interlayer film on the modified surface, making the polyvinyl butyral interlayer film flat and adhered to the modified surface. Then, place another piece of modified semi-tempered glass with the modified surface facing down on the polyvinyl butyral interlayer film, so that the polyvinyl butyral interlayer film is located between the modified surfaces of the two pieces of modified semi-tempered glass, to obtain laminated glass. Roll press the laminated glass to pre-vent air and remove residual air from the laminated glass, to obtain pre-vented laminated glass. Then, place the pre-vented laminated glass in an autoclave, keep it at 125°C for 30 minutes, and cool it to obtain semi-tempered laminated glass.
[0047] S4. Weigh 20g of 3A molecular sieve and fill it into the aluminum alloy spacer strip to seal the port. Apply 30g of butyl hot melt sealant to both sides of the aluminum alloy spacer strip. The butyl hot melt sealant is applied at a temperature of 120℃. Press the semi-tempered laminated glass obtained in S3, the aluminum alloy spacer strip, and the semi-tempered glass obtained in S2 together to form a hollow cavity. Fill the hollow cavity with argon gas to obtain glass filled with argon gas. Inject 160g of two-component polysulfide sealant along the outer channel of the argon-filled glass and cure for 24h to obtain semi-tempered laminated insulating glass.
[0048] Preparation steps of cerium-zirconium-aluminum-silicon-boron complex toughening sol:
[0049] A1. Weigh 55g of anhydrous ethanol, 18g of deionized water, and 0.2g of glacial acetic acid and add them to a reactor. Stir at 20°C to ensure the anhydrous ethanol, deionized water, and glacial acetic acid are mixed evenly. Then weigh 18g of tetraethyl orthosilicate and add it to the reactor. Continue stirring to disperse the tetraethyl orthosilicate in the system formed by the anhydrous ethanol, deionized water, and glacial acetic acid and allow it to undergo pre-hydrolysis, obtaining a silicate ester pre-hydrolyzed mixture. Add 4g of γ-glycidoxypropyltrimethoxysilane to the silicate ester pre-hydrolyzed mixture and continue stirring to ensure the γ-glycidoxypropyltrimethoxysilane is fully mixed with the silicate ester pre-hydrolyzed mixture. Then add 0.6g of boric acid and 0.5g of citric acid monohydrate, heat to 35°C, and react for 1 hour. After the reaction is complete, a borosilicate pre-hydrolyzed solution is obtained.
[0050] A2. Weigh 35g of deionized water, 20g of anhydrous ethanol and 8g of citric acid monohydrate and add them to another reactor. Stir to dissolve the citric acid monohydrate and form a homogeneous system. Then add 3g of zirconium oxynitrate hydrate, 2g of aluminum nitrate nonahydrate and 0.8g of cerium nitrate hexahydrate in sequence. Continue stirring to fully disperse the zirconium oxynitrate hydrate, aluminum nitrate nonahydrate and cerium nitrate hexahydrate. Add 2g of ethylene glycol, continue stirring and then add ammonia water to adjust the pH to 3.5. Heat to 45℃ and react for 1.5h. After the reaction is completed, a cerium-zirconium-aluminum complex solution is obtained.
[0051] A3. The cerium-zirconium-aluminum complex solution obtained in A2 is added dropwise to the silicon-boron pre-hydrolyzed solution obtained in A1. During the dropwise addition, the mixture is continuously stirred to ensure that the cerium-zirconium-aluminum complex solution and the silicon-boron pre-hydrolyzed solution are fully mixed. After the dropwise addition is completed, the mixture is stirred again, and ammonia is added to adjust the pH to 4.0. Then, 0.2 g of polyvinylpyrrolidone is added, and the mixture is reacted at 45 °C for 3 h. After the reaction is completed, a cerium-zirconium-aluminum-silicon-boron composite complex colloid is obtained.
[0052] A4. The cerium-zirconium-aluminum-silicon-boron composite complex colloid obtained in A3 was aged in a sealed container at 35°C for 12 hours to obtain an aged colloid. The aged colloid was then distilled under reduced pressure at 45°C to remove some volatile components, resulting in a concentrated colloid. 10g of anhydrous ethanol and 5g of deionized water were added to the concentrated colloid, stirred evenly, and the pH was adjusted to 4.2. The colloid was filtered, and the filtrate was collected to obtain the cerium-zirconium-aluminum-silicon-boron complex toughening sol.
[0053] Example 3
[0054] The difference between this embodiment and Embodiment 1 is that this embodiment provides a manufacturing process for semi-tempered laminated insulating glass, including the following steps:
[0055] S1. Cut, grind, and chamfer the edges of the soda-lime-silicon glass to make the edges smooth, thus obtaining pre-treated glass. Weigh 2.0g of octylphenol polyoxyethylene ether and add it to 300g of deionized water. Stir to disperse the octylphenol polyoxyethylene ether evenly, thus obtaining a cleaning solution. Wash the pre-treated glass with the cleaning solution to remove grinding residues and oil stains from the surface of the pre-treated glass. Rinse with deionized water to remove residual cleaning solution. Dry for 8 minutes to obtain glass to be semi-tempered.
[0056] S2. The glass to be semi-tempered obtained in S1 is sent into a tempering furnace and heated at 690℃ to achieve a semi-tempered state. Then, it is subjected to rapid cooling to obtain semi-tempered glass. Weigh 2.0g of cerium-zirconium-aluminum-silicon-boron complex toughening sol, 95g of anhydrous ethanol and 15g of deionized water, mix and stir to uniformly disperse the cerium-zirconium-aluminum-silicon-boron complex toughening sol to obtain an interface treatment solution. Coat the interface treatment solution onto the surface of the semi-tempered glass to be laminated and dry at 70℃ for 15min to form a modified layer on the surface of the semi-tempered glass to be laminated, thus obtaining modified semi-tempered glass.
[0057] S3. Place the modified semi-tempered glass at 25°C. The modified semi-tempered glass has a modified surface and a non-modified surface. The modified surface is the side surface coated with the interface treatment liquid. Place one piece of modified semi-tempered glass with the modified surface facing up. Lay 60g of polyvinyl butyral interlayer film on the modified surface, making the polyvinyl butyral interlayer film flat and adhered to the modified surface. Then, place another piece of modified semi-tempered glass with the modified surface facing down on the polyvinyl butyral interlayer film, so that the polyvinyl butyral interlayer film is located between the modified surfaces of the two pieces of modified semi-tempered glass, to obtain laminated glass. Roll press the laminated glass to pre-vent air and remove residual air from the laminated glass, to obtain pre-vented laminated glass. Then, place the pre-vented laminated glass in an autoclave and keep it at 140°C for 60 minutes. Cool it to obtain semi-tempered laminated glass.
[0058] S4. Weigh 20g of 3A molecular sieve and fill it into the aluminum alloy spacer strip to seal the port. Apply 30g of butyl hot melt sealant to both sides of the aluminum alloy spacer strip. The butyl hot melt sealant is applied at a temperature of 140℃. Press the semi-tempered laminated glass obtained in S3, the aluminum alloy spacer strip, and the semi-tempered glass obtained in S2 together to form a hollow cavity. Fill the hollow cavity with argon gas to obtain glass filled with argon gas. Inject 160g of two-component polysulfide sealant along the outer channel of the argon-filled glass and cure for 72h to obtain semi-tempered laminated insulating glass.
[0059] Preparation steps of cerium-zirconium-aluminum-silicon-boron complex toughening sol:
[0060] A1. Weigh 75g of anhydrous ethanol, 28g of deionized water, and 0.8g of glacial acetic acid and add them to a reactor. Stir at 30°C to ensure the anhydrous ethanol, deionized water, and glacial acetic acid are mixed evenly. Then weigh 26g of tetraethyl orthosilicate and add it to the reactor. Continue stirring to disperse the tetraethyl orthosilicate in the system formed by the anhydrous ethanol, deionized water, and glacial acetic acid and allow it to undergo pre-hydrolysis, obtaining a silicate ester pre-hydrolyzed mixture. Add 8g of γ-glycidoxypropyltrimethoxysilane to the silicate ester pre-hydrolyzed mixture and continue stirring to ensure the γ-glycidoxypropyltrimethoxysilane is fully mixed with the silicate ester pre-hydrolyzed mixture. Then add 1.6g of boric acid and 1.2g of citric acid monohydrate, heat to 45°C, and react for 2 hours. After the reaction is complete, a borosilicate pre-hydrolyzed solution is obtained.
[0061] A2. Weigh 55g of deionized water, 35g of anhydrous ethanol, and 14g of citric acid monohydrate and add them to another reactor. Stir to dissolve the citric acid monohydrate and form a homogeneous system. Then, add 6g of zirconium oxynitrate hydrate, 5g of aluminum nitrate nonahydrate, and 2.2g of cerium nitrate hexahydrate in sequence. Continue stirring to fully disperse the zirconium oxynitrate hydrate, aluminum nitrate nonahydrate, and cerium nitrate hexahydrate. Add 5g of ethylene glycol, continue stirring, and then add ammonia water to adjust the pH to 4.0. Heat to 60℃ and react for 3 hours. After the reaction is complete, a cerium-zirconium-aluminum complex solution is obtained.
[0062] A3. The cerium-zirconium-aluminum complex solution obtained in A2 is added dropwise to the silicon-boron pre-hydrolyzed solution obtained in A1. During the dropwise addition, the mixture is continuously stirred to ensure that the cerium-zirconium-aluminum complex solution and the silicon-boron pre-hydrolyzed solution are fully mixed. After the dropwise addition is completed, the mixture is stirred again, and ammonia is added to adjust the pH to 4.5. Then, 0.8 g of polyvinylpyrrolidone is added, and the mixture is reacted at 55 °C for 5 h. After the reaction is completed, a cerium-zirconium-aluminum-silicon-boron composite complex colloid is obtained.
[0063] A4. The cerium-zirconium-aluminum-silicon-boron composite complex colloid obtained in A3 was aged in a sealed container at 45°C for 24 hours to obtain an aged colloid. The aged colloid was then distilled under reduced pressure at 55°C to remove some volatile components, resulting in a concentrated colloid. 30g of anhydrous ethanol and 20g of deionized water were added to the concentrated colloid, stirred evenly, and the pH was adjusted to 4.6. The colloid was filtered, and the filtrate was collected to obtain the cerium-zirconium-aluminum-silicon-boron complex toughening sol.
[0064] Comparative Example 1
[0065] The difference between this comparative example and Example 1 is that 1.25g of cerium-zirconium-aluminum-silicon-boron complex toughening sol is not added in step S2, while the rest is the same as in Example 1.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 is that step A2 is omitted in the preparation of the cerium-zirconium-aluminum-silicon-boron complex toughening sol; the rest is the same as in Example 1.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that 6g of γ-glycidoxypropyltrimethoxysilane is not added in step A1, while the rest is the same as in Example 1.
[0070] A series of standardized tests were conducted on the semi-tempered laminated insulated glass manufactured using the manufacturing processes described in Examples 1-3 and Comparative Examples 1-3.
[0071] Semi-tempered laminated insulating glass prepared in Examples 1-3 and Comparative Examples 1-3 were used as test samples. The number of test samples in each group was 3. Before the test, the samples were placed in an environment of 23°C and 50% relative humidity for 24 hours to equilibrate. The test result was the average value of the 3 samples.
[0072] For the initial peel strength test, semi-tempered laminated glass was cut into test strips with a width of 25 mm from the edge. A 30 mm pre-peel was performed along the interface between the polyvinyl butyral interlayer film and the modified semi-tempered glass. The glass side was fixed in the fixture, and the polyvinyl butyral interlayer film side was connected to the tension fixture. Peeling was performed at 180° at a speed of 100 mm / min at 23°C. The average peel force during the stable peeling stage was recorded and converted into the initial peel strength according to the width of the test strip.
[0073] When testing the peel strength retention rate after damp heat aging, the sample was placed in a constant temperature and humidity chamber at 85℃ and 85% relative humidity for 1000 hours. After being taken out, it was placed in an environment at 23℃ for 24 hours to equilibrate. Then, the peel strength after aging was measured according to the initial peel strength test method, and the peel strength retention rate after damp heat aging was calculated according to the ratio of the peel strength after aging to the initial peel strength.
[0074] During the edge debonding width test, the sample after wet heat aging was placed in front of a uniform white background. The whitening, bubbling, and debonding areas on the glass edge were observed with the naked eye. A vernier caliper with a resolution of 0.01 mm was used to measure the maximum distance the debonding area extended inward from the edge along the four sides of the sample. The maximum value was taken as the edge debonding width.
[0075] During the dew point test of the hollow cavity, after the sample is equilibrated in an environment of 23℃ for 24 hours, the dew point test probe is placed close to the glass surface corresponding to the hollow cavity, and the temperature of the test probe is gradually reduced. The inner surface of the hollow cavity is observed to see if condensation or frost appears. The temperature at which condensation or frost first appears is recorded as the dew point of the hollow cavity.
[0076] During the heat transfer coefficient test, the sample is installed in a steady-state heat transfer test device, and the set temperature difference is maintained on both sides of the sample. After the heat flux density stabilizes, the heat flux density, hot side temperature and cold side temperature are continuously recorded for 30 minutes. The heat transfer coefficient is calculated based on the ratio of the stable heat transfer per unit area to the temperature difference between the two sides.
[0077] During the drop ball impact fragment retention rate test, the sample is fixed horizontally so that the impact point is located in the center area of the sample. A steel ball is dropped freely from a set height to impact the center of the sample. After the impact, glass fragments that have detached from the sample are collected and weighed. At the same time, the total fragment mass corresponding to the broken area is weighed. The fragment retention rate after drop ball impact is calculated according to the proportion of the mass of the fragments that have not detached to the total fragment mass of the broken area.
[0078] The performance test data above are shown in Table 1.
[0079] Table 1 Performance Test Results
[0080]
[0081] As can be seen from the above, Examples 1-3 significantly solve the technical problems of insufficient bonding stability of the interlayer of existing semi-tempered laminated insulating glass, easy debonding after humid heat aging, whitening and blistering at the edges, decreased sealing reliability of the hollow cavity, and insufficient fragment retention capacity after impact compared with Comparative Examples 1-3.
[0082] The initial peel strengths of Examples 1-3 were 8.7 N / mm, 7.9 N / mm, and 8.4 N / mm, respectively, which were significantly higher than those of Comparative Example 1 (4.6 N / mm), Comparative Example 2 (6.1 N / mm), and Comparative Example 3 (6.5 N / mm). This indicates that the interface treatment layer formed by using cerium-zirconium-aluminum-silicon-boron complex toughening sol can effectively enhance the interfacial bonding between the semi-tempered glass and the polyvinyl butyral interlayer film.
[0083] The peel strength retention rates after humid heat aging in Examples 1-3 reached 91.8%, 88.5% and 90.6% respectively, which were significantly higher than those of Comparative Example 1 (56.3%), Comparative Example 2 (72.4%) and Comparative Example 3 (76.8%). This indicates that the complete cerium-zirconium-aluminum-silicon-boron complex toughening sol can maintain the stability of the interface layer under humid heat conditions and reduce the damage of moisture to the interlayer.
[0084] The edge debonding widths of Examples 1-3 were only 0.4mm, 0.6mm, and 0.5mm, respectively, while those of Comparative Examples 1-3 reached 3.8mm, 2.1mm, and 1.7mm, respectively. This indicates that the examples can effectively suppress edge whitening, blistering, and debonding expansion, and solve the problem of insufficient moisture and heat resistance at the edges of existing laminated insulated glass.
[0085] The dew points of the hollow cavities in Examples 1-3 were -47℃, -44℃, and -46℃, respectively, which were lower than those in Comparative Example 1 (-34℃), Comparative Example 2 (-39℃), and Comparative Example 3 (-40℃). This indicates that improving the stability of the interlayer can reduce the adverse effects of moisture migration at the edges on the hollow cavity and improve the reliability of the hollow seal.
[0086] The heat transfer coefficients of Examples 1-3 are 1.58 W / (m²). 2 ·K), 1.62W / (m 2 ·K) and 1.56W / (m 2 ·K), lower than the 1.71W / (m³) of comparative examples 1-3. 2 ·K), 1.66W / (m 2 ·K) and 1.64W / (m 2 The presence of K indicates that the hollow cavity has a better sealing state and argon gas retention effect, which is beneficial to improving the thermal insulation performance.
[0087] The fragment retention rates after ball impact in Examples 1-3 were 98.6%, 97.9%, and 98.3%, respectively, which were higher than those of Comparative Example 1 (91.2%), Comparative Example 2 (94.8%), and Comparative Example 3 (95.5%). This indicates that the modified interface layer improved the adhesion and retention ability of the polyvinyl butyral interlayer film to glass fragments.
[0088] Comparative Example 1, without the addition of cerium-zirconium-aluminum-silicon-boron complex toughening sol, showed the most significant decrease in all properties, indicating that the sol as a whole plays a key role in interface reinforcement and hygrothermal stability.
[0089] Comparative Example 2 lacks the cerium-zirconium-aluminum complex structure, and its peel strength retention rate and edge debonding performance are significantly worse than those of the Example, indicating that the zirconium, aluminum, and cerium complex structure plays an important role in improving the density and water erosion resistance of the interface layer.
[0090] Comparative Example 3 lacked γ-glycidoxypropyltrimethoxysilane, and its initial peel strength and wet heat retention were lower than those of the Example, indicating that the silane component plays an important role in enhancing the bonding between the glass interface layer and the polyvinyl butyral interlayer film.
[0091] In summary, Examples 1-3 effectively solved the technical problems of weak interfacial bonding, poor edge resistance to moisture and heat, insufficient durability of the insulated seal, and low breakage retention capacity of existing semi-tempered laminated insulating glass through octylphenol polyoxyethylene ether cleaning, semi-tempered treatment, cerium-zirconium-aluminum-silicon-boron complex toughening sol interface modification, polyvinyl butyral interlayer film composite, and synergistic effect of hollow sealing.
Claims
1. A manufacturing process for semi-tempered laminated insulating glass, characterized in that, Includes the following steps: S1. Cut, grind, and chamfer the soda-lime-silica glass to obtain pretreated glass; Add 0.5-2.0 parts by weight of octylphenol polyoxyethylene ether to 200-300 parts of deionized water and stir to obtain a cleaning solution; The pre-treated glass is washed with cleaning solution, then rinsed with deionized water and dried to obtain glass to be semi-tempered. S2. The glass to be semi-tempered is sent into a tempering furnace and heated at 650-690℃, followed by rapid cooling to obtain semi-tempered glass. By weight, 0.5-2.0 parts of cerium-zirconium-aluminum-silicon-boron complex toughening sol, 80-95 parts of anhydrous ethanol and 5-15 parts of deionized water are mixed and stirred to obtain an interface treatment solution; the interface treatment solution is coated on the surface of the semi-tempered glass to be laminated and dried at 50-70℃ to obtain modified semi-tempered glass. S3. Place two pieces of modified semi-tempered glass at 20-25℃. The modified semi-tempered glass has a modified surface and an unmodified surface. The modified surface is the side surface coated with the interface treatment liquid. Place one piece of modified semi-tempered glass with the modified surface facing up, and lay a polyvinyl butyral interlayer film on the modified surface. Then, place another piece of modified semi-tempered glass with the modified surface facing down on the polyvinyl butyral interlayer film, so that the polyvinyl butyral interlayer film is located between the modified surfaces of the two pieces of modified semi-tempered glass to obtain laminated glass. Roll press the laminated glass and pre-vent the air to obtain pre-vented laminated glass. Then, place the pre-vented laminated glass in an autoclave, keep it at 125-140℃, and cool it to obtain semi-tempered laminated glass. S4. Fill the aluminum alloy spacer with 3A molecular sieve, seal the port, and apply butyl hot melt sealant to both sides of the aluminum alloy spacer. Press the semi-tempered laminated glass, aluminum alloy spacer and semi-tempered glass together to form a hollow cavity. Fill the hollow cavity with argon gas to obtain glass filled with argon gas. Two-component polysulfide sealant is injected along the outer perimeter of the argon-filled glass and allowed to cure. The preparation steps of the cerium-zirconium-aluminum-silicon-boron complex toughening sol include: A1. By weight, add 55-75 parts anhydrous ethanol, 18-28 parts deionized water, and 0.2-0.8 parts glacial acetic acid to a reactor and stir at 20-30°C; then add 18-26 parts tetraethyl orthosilicate and continue stirring to obtain a silicate ester pre-hydrolyzed mixture; add 4-8 parts γ-glycidoxypropyltrimethoxysilane to the silicate ester pre-hydrolyzed mixture and continue stirring; then add 0.6-1.6 parts boric acid and 0.5-1.2 parts citric acid monohydrate, and react at 35-45°C to obtain a borosilicate pre-hydrolyzed solution; A2. Add 35-55 parts deionized water, 20-35 parts anhydrous ethanol and 8-14 parts citric acid monohydrate to the reactor and stir. Then add 3-6 parts zirconium oxynitrate hydrate, 2-5 parts aluminum nitrate nonahydrate and 0.8-2.2 parts cerium nitrate hexahydrate in sequence and continue stirring. Add 2-5 parts ethylene glycol and then add ammonia water to adjust the pH to 3.5-4.
0. Heat to 45-60℃ to react and obtain cerium-zirconium-aluminum complex solution. A3. Add the cerium-zirconium-aluminum complex solution dropwise to the silicon-boron pre-hydrolyzed solution and stir; add ammonia water to adjust the pH to 4.0-4.5, then add 0.2-0.8 parts of polyvinylpyrrolidone and react at 45-55℃ to obtain the cerium-zirconium-aluminum-silicon-boron composite complex colloid. A4. The cerium-zirconium-aluminum-silicon-boron composite complex colloid is aged in a sealed environment at 35-45℃ to obtain an aged colloid; the aged colloid is distilled under reduced pressure at 45-55℃ to obtain a concentrated colloid; 10-30 parts of anhydrous ethanol and 5-20 parts of deionized water are added to the concentrated colloid to adjust the pH to 4.2-4.6; then the mixture is filtered.
2. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step S1, the drying time is 3-8 minutes.
3. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step S2, the drying time at 50-70℃ is 5-15 minutes.
4. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step S3, the heat preservation time at 125-140℃ is 30-60 minutes.
5. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step S4, the butyl hot melt sealant is applied at a temperature of 120-140℃ and cured for 24-72 hours.
6. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step A1, the reaction time is 1-2 hours after heating to 35-45℃.
7. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step A2, the reaction time is 1.5-3 hours after heating to 45-60℃.
8. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step A3, the reaction time is 3-5 hours at 45-55℃.
9. The manufacturing process of semi-tempered laminated insulating glass according to claim 1, characterized in that, In step A4, the curing time in a sealed environment at 35-45℃ is 12-24 hours.
Citation Information
Patent Citations
Interlayer hollow glass and preparation method thereof
CN118637842A
Preparation method and application of silicon-zirconium sol cured at normal temperature
CN121718196A
Glass laminates with improved weatherability
US20080318063A1